Correlation of Angiographic Circulation Time and Cerebrovascular Reserve by Acetazolamide-Challenged Single Photon Emission CT - Yamamoto, Shiro (AJNR Am J Neuroradiol, 2004)
BACKGROUND AND PURPOSE: Although cerebral circulation time (CCT) is one of the main parameters in cerebral blood flow measurements, its clinical significance is controversial. To assess the importance of CCT by using a nondiffusible indicator, we studied the relationship between angiographic CCT and cerebrovascular reserve. METHODS: Twenty-eight patients, each with a unilateral occlusive lesion in the internal carotid artery or middle cerebral artery, were examined. To assess the CCT, the regional arteriocapillary circulation time (rACCT) was measured by angiography and the ratio of the value on the occlusive side to the value on the contralateral side was calculated as the rACCT ratio. To estimate the cerebrovascular reserve, acetazolamide-challenged single photon emission CT was used. Patients with a decreased cerebrovascular reserve were defined as the “poor reserve” group, and those without a decrease were defined as the “normal reserve” group. The ratio of the radioactivity count on the occlusive side to the count on the contralateral side was calculated as the asymmetry index, and the proportion of the acetazolamide-challenged asymmetry index to the baseline asymmetry index was defined as the regional reactivity index. RESULTS: The rACCT ratio in the poor reserve group (n = 19) was significantly (P < .001) larger than that in the normal reserve group (n = 9), and a significant correlation (r = −0.83, P < .01) was found between the rACCT ratio and the regional reactivity index. CONCLUSION: The angiographic CCT and the cerebral vasoreactivity to acetazolamide on single photon emission CT were well correlated, suggesting that measurement of the CCT by using a nondiffusible indicator could be used as an index of cerebrovascular reserve.